2015
DOI: 10.1155/2015/795357
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Bypass Implantation for Primary Open-Angle Glaucoma Combined with Phacoemulsification: 4-Year Follow-Up

Abstract: Purpose. To report the long-term follow-up results in patients with cataract and primary open-angle glaucoma (POAG) randomly assigned to cataract surgery combined with micro-bypass stent implantation or phacoemulsification alone. Methods. 36 subjects with cataract and POAG were randomized in a 1 : 2 ratio to either iStent implantation and cataract surgery (combined group) or cataract surgery alone (control group). 24 subjects agreed to be evaluated again 48 months after surgery. Patients returned one month lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 10 publications
2
62
0
3
Order By: Relevance
“…To date, this device has amassed a sizable longterm evidence base regarding its safety and performance in eyes with open-angle glaucoma, in settings both with and without cataract surgery. Most studies of the device have assessed outcomes in mild to moderate glaucoma [17][18][19][20][21][22][23][24][25][26][27], but other patient populations increasingly have been the subject of evaluation, such as pseudoexfoliative glaucoma, severe or refractory glaucoma, or newly diagnosed, treatment-naïve glaucoma [28][29][30][31][32][33]. Another growing and relevant area of investigation has been economics outcomes research [34][35][36][37][38][39], which consistently has shown favorable cost-effectiveness of the iStent in various healthcare models around the world.…”
Section: Introductionmentioning
confidence: 99%
“…To date, this device has amassed a sizable longterm evidence base regarding its safety and performance in eyes with open-angle glaucoma, in settings both with and without cataract surgery. Most studies of the device have assessed outcomes in mild to moderate glaucoma [17][18][19][20][21][22][23][24][25][26][27], but other patient populations increasingly have been the subject of evaluation, such as pseudoexfoliative glaucoma, severe or refractory glaucoma, or newly diagnosed, treatment-naïve glaucoma [28][29][30][31][32][33]. Another growing and relevant area of investigation has been economics outcomes research [34][35][36][37][38][39], which consistently has shown favorable cost-effectiveness of the iStent in various healthcare models around the world.…”
Section: Introductionmentioning
confidence: 99%
“…A large RCT performed by Craven et al demonstrated modest IOP reduction of 1.5 mmHg from preoperative medicated IOP levels with a corresponding decrease in medications from 1.6 ± 0.8 to 0.3 ± 0.6 [17], while another large RCT by Samuelson found an equally modest IOP reduction of 1.5 mmHg after 1 year with a decrease in medication from 1.5 ± 0.6 to 0.2 ± 0.6 [18]. Two other smaller RCTs by Fea et al found similar IOP reductions and medication reduction to 0.5 medication or less [19, 20] (Table 2). In some RCTs, there was a specified medication washout period postoperatively and the authors found postoperative IOP to be around 17 mmHg [10, 16].…”
Section: Resultsmentioning
confidence: 99%
“…The common control arm of cataract surgery as a single procedure allowed for indirect comparison of alternative MIGS. The widely used ITC method described by Bucher and collaborators was used, which allows for an adjusted estimation of the effects without compromising the original trial randomization [17]. In alignment with the evidence found, a total of three ITCs were feasible, as outlined in Fig.…”
Section: Indirect Treatment Comparison and Combined Treatment Effectsmentioning
confidence: 99%